Balidāna-smārikā : amara hutātmā Svāmī Śraddhānanda Jī Mahārāja - Sraddhananda, Swami (Dillī Ārya Pratinidhi Sabhā, 1976)
Souvenir issued to commemorate the 50th death anniversary of Swami Sraddhananda, 1857-1926, leader of Arya-Samaj and patriot.